Integrated omics approaches for flax improvement under abiotic and biotic stress: Current status and future prospects - Yadav, Bindu; Kaur, Vikender; Narayan, Om Prakash; Yadav, Shashank Kumar; Kumar, Ashok; Wankhede, Dhammaprakash Pandhari (Frontiers in Plant Science, 2022)
Flax (Linum usitatissimum L.) or linseed is one of the important industrial crops grown all over the world for seed oil and fiber. Besides oil and fiber, flax offers a wide range of nutritional and therapeutic applications as a feed and food source owing to high amount of -linolenic acid (omega-3 fatty acid), lignans, protein, minerals and vitamins. Periodic losses caused by unpredictable environmental stresses such as drought, heat, salinity-alkalinity and diseases pose a threat to meet the rising market demand. Furthermore, these abiotic and biotic stressors have a negative impact on biological diversity and quality of oil/fiber. Therefore, understanding the interaction of genetic and environmental factors in stress tolerance mechanism and identification of underlying genes for economically important traits is critical for flax improvement and sustainability. In recent technological era, numerous omics techniques such as genomics, transcriptomics, metabolomics, proteomics, phenomics, and ionomics have evolved and fascinated researchers. The advancements in genomics have made quantitative trait loci (QTL) mapping, genome-wide association studies (GWAS), and genomic selection easier in major cereal and oilseed crops including flax. Extensive studies in the area of genomics and transcriptomics have been conducted subsequent upon flax genome sequencing and availability of genetic maps. Interestingly, more research has been focused for abiotic stresses tolerance compared to disease resistance in flax transcriptomics, while the other areas of omics such as metabolomics, proteomics, ionomics and phenomics is in the initial stages in flax and several key questions remain unanswered. Little has been explored in the integration of omic-scale data to explain complex genetic, physiological and biochemical basis of stress tolerance in flax. In this review, the current status of various omics approaches for elucidation of molecular pathways underlying abiotic and biotic stress tolerance in flax have been presented and the importance of integrated omics technologies in future research and breeding have been emphasized to ensure sustainable yield in challenging environments.